The effect of country image, brand image, and warranty knowledge on car purchase intentions: a comparison of use situations - Albert Kriestian Novi Adhi Nugraha; Cara Edo Krista; Andrian Dolfriandra Huruta (Cogent Business & Management, 2024)
Country image, brand image, and warranty knowledge are essential for evaluation and decision-making. This study examines the effects of these three variables on the purchase intentions of a car as a high-involvement product with high-risk attributes. This study investigates the role of consumer knowledge of essential product external cues, namely product warranty, which is relevant mainly for risk-averse consumers. Specifically, the present research tests the moderating effects of two categories of product warranty knowledge, subjective and objective, on the relationship between country image and brand image on purchase intentions in two different consumption situations: personal and business. The current study applies a quantitative approach and collected data through a survey of 386 respondents who are the owners and managers of car rental service providers in Central Java, Indonesia. The hypothesis was tested using structural equation modeling, and the findings indicate the significant effects of country image and brand image on purchase intentions in personal and business settings. Further tests demonstrate that only subjective warranty knowledge moderates the relationship between country image and purchase intentions but not the relationship between brand image and purchase intentions in personal and business backgrounds. This study offers several managerial implications for future research, particularly when comparing the models of individual and business consumers.
Keywords: 650; Country image; brand image; subjective warranty knowledge; objective warranty knowledge; purchase intentions